PELAKSANAAN KEBIJAKAN KEPENDUDUKAN PENDUDUK RENTAN ADMINISTRASI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KAMPAR - Gustina, Riri; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research is to analyze the implementation of the policy and the factors which influence The implementation of the population policy of the vulnerable population department of population and civil regristation district Kampar.This research uses qualitative approach. The result of this research shows that The implementation of the population policy of the vulnerable population department of population and civil regristation district Kampar based on the interviews with employees of the administration vulnerable population,people who have vulnerable administration, people who have not vulnerable administration, district, RT, RW that the implementation of the population policy of the vulnerable population at department of population and civil regristation district Kampar is not optimalIt is seen from the data collection team which is not provided by the departement of population and civil regristation for vulnerable population administration, lack of SOP, lack of the employees and also lack of the facilities to support the work which make it is very hard to coordinate the population who come and move from the district.Keywords : The policy implementation and administration of the vulnerable population